Effects of dietary factors on iron status and body mass index in students - Niaz Hussain Jamali; Zulfiqar Ali Laghari; Anwar Ali Jamali; Arsalan Ahmer; Rao Irfan; Ishfaque Nazir; Jamshaid Warsi; Hamid Ali Kazi (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: The objective of this study was to analysing the correlation between dietary factors, including meat, milk, egg and fruit to Serum ferritin (S.f) and Haemoglobin (Hb) concentration in students. Methods: In this cross sectional study, 1686 normal volunteers were randomly selected from Government Schools during the period of September 2015 to April 2016. Data concerning dietary intake such as meat, milk, egg and fruits were taken. Baseline levels for volunteers were specified after collection of data like personal, anthropometery and dietary intake to determine Hb and S.f levels. Results: Observation of mean values such as 18.7kg/m2 for Body Mass Index (BMI), 12.2g/dl for Haemoglobin and 88.0µg/l for Serum ferritin were taken from all samples. The mean values for Hb 14.6g/dl, S.f 190.0µg/l, and BMI 21.50kg/m2 were higher for volunteers with high meat intake as compared to other dietary elements. However, dietary factors such as meat, egg and fruits showed significant association with Hb, S.f, BMI and monthly income, however milk consumption has non significant association with haemoglobin at P<0.01 level. Conclusion: Iron status in blood is significantly affected by dietary intake such as meat, milk, fruits and eggs. However, dietary habits in population are highly affected by other socioeconomic factors such as lifestyle and income. Although dietary intake on daily basis, enhanced the Hb and Serum ferritin levels, but meat takers showed higher values than other food components so it is recommended that meat should be taken more for the management of Iron Deficiency Anemia (IDA). Continuous...